2015
DOI: 10.1097/ccm.0000000000000789
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Aspirin Use Is Associated With Reduced Risk of Acute Respiratory Distress Syndrome in Critically Ill Patients

Abstract: Objectives Platelet activation plays an active role in the pathogenesis of acute respiratory distress syndrome (ARDS). In our prior study of 575 patients at high risk for ARDS, concurrent statin and aspirin use was associated with reduced ARDS. However, the largest study (n=3855) to date found no significant benefit of prehospital aspirin in a lower risk population when adjusted for the propensity for aspirin use. We aimed to determine whether prehospital aspirin use is associated with decreased ARDS in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(107 citation statements)
references
References 33 publications
3
102
0
1
Order By: Relevance
“…For high risk of ARDS, preventive strategies may be required such as protective MV optimization (low tidal volume, high PEEP), restrictive transfusion, sepsis management, as well as conservative fluid strategy (29). Furthermore, some novel treatments are now under investigations but they are all based on early recognition of ARDS, such as prehospital use of inhaled steroids, aspirin, or heparin (30)(31)(32). Our study about the risk factors for ARDS development in severe pneumonia further enriches and highlights the limited knowledge in such an area and is of clinical importance and practice.…”
Section: Discussionmentioning
confidence: 99%
“…For high risk of ARDS, preventive strategies may be required such as protective MV optimization (low tidal volume, high PEEP), restrictive transfusion, sepsis management, as well as conservative fluid strategy (29). Furthermore, some novel treatments are now under investigations but they are all based on early recognition of ARDS, such as prehospital use of inhaled steroids, aspirin, or heparin (30)(31)(32). Our study about the risk factors for ARDS development in severe pneumonia further enriches and highlights the limited knowledge in such an area and is of clinical importance and practice.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the opportunity for ARDS prevention is constrained in a small window of time [31]. Some observational studies and experimental data suggested a potential preventive role of antiplatelet therapy in patients at high risk of ARDS [32][33][34]. As ARDS pathogenesis includes a series of dysregulated mechanisms (e.g.…”
Section: Preventionmentioning
confidence: 99%
“…There are several very recent human studies concerning the antiplatelet therapy in ARDS. Regarding the prevention of ARDS, the administration of antiplatelet treatment in patients with at least one risk factor led to a reduced incidence of the syndrome [131] . However, these results were not confirmed in a larger trial studying the prehospital administration of aspirin, which showed only a trend towards reduced occurrence of the syndrome [132] .…”
Section: The Role Of Platelets and Immune Cells In The Resolution Of mentioning
confidence: 99%